Skip to content

Instantly share code, notes, and snippets.

@kbuzzard
Last active February 24, 2023 18:22
Show Gist options
  • Star 8 You must be signed in to star a gist
  • Fork 0 You must be signed in to fork a gist
  • Save kbuzzard/b337639d471a135108511f4fab850e8b to your computer and use it in GitHub Desktop.
Save kbuzzard/b337639d471a135108511f4fab850e8b to your computer and use it in GitHub Desktop.
IMO 2019 Q1 solution formalised in Lean
-- this was compiling with mathlib in June 2020
import tactic
theorem imo2019Q1 (f : ℤ → ℤ) :
(∀ a b : ℤ, f (2 * a) + 2 * (f b) = f (f (a + b))) ↔
(∀ x, f x = 0) ∨ ∃ c, ∀ x, f x = 2 * x + c :=
begin
split, swap,
{ -- easy way: f(x)=0 and f(x)=2x+c work.
intro h,
cases h,
{ -- zero function works
intros a b,
rw [h (2 * a), h b, h (f (a + b))],
simp
},
{ -- f(x)=2x+c works
intros a b,
cases h with c h,
repeat {rw h},
ring
},
},
-- hard way.
intro h, -- functional equation
-- a=b=0 and a=-1,b=1 give this:
have h0 : f 0 + 2 * f 0 = f(-2) + 2 * f 1,
convert h 0 0,
convert h (-1) 1,
-- a=0 gives this:
have h1 : ∀ b, f 0 + 2 * f b = f (f b),
intro b, convert h 0 b, simp,
-- a=-1 gives this:
have h2 : ∀ b, f (-2) + 2 * f (b + 1) = f (f b),
intro b, convert h (-1) (b+1); ring,
-- equating right hand sides of h1 and h2 gives this:
have h3 : ∃ m, ∀ b, f (b + 1) - f b = m,
use f 1 - f 0,
intro b,
apply (domain.mul_left_inj (show (2 : ℤ) ≠ 0, from dec_trivial)).1,
rw sub_mul,
have h4 : f (b + 1) * 2 = f (f b) - f (-2),
rw [←h2 b], simp [mul_comm],
have h5 : f b * 2 = f (f b) - f 0,
rw [←h1 b], simp [mul_comm],
rw [h4, h5],
rw eq_sub_of_add_eq h0.symm,
ring,
cases h3 with m h3,
-- h3 and induction on b (upwards and downwards) gives this:
have h4 : ∀ b, f b = m * b + f 0,
intro b,
apply int.induction_on' b 0, simp,
{ intros k hk hf,
rw [eq_add_of_sub_eq (h3 k), hf],
ring
},
{ intros k hk hf,
have h4 := h3 (k - 1),
replace h4 := eq_add_of_sub_eq h4,
rw add_comm m at h4,
replace h4 := eq_sub_of_add_eq h4.symm,
rw h4,
rw add_comm at hf,
rw eq_sub_of_add_eq hf.symm,
rw sub_add_cancel,
ring,
},
-- now sub h4 into h
conv at h in (f (2 * _) + 2 * f _ = f (f (_))) begin
rw h4 (2 * a),
rw h4 b,
rw h4 (a + b),
rw h4 (m * (a + b) + f 0),
end,
-- and now it's straightforward from a=b=0 and a=0,b=1.
have h5 : 2 * f 0 = m * f 0,
{ have h6 := h 0 0,
simp at h6,
linarith [h6],
},
by_cases h6 : f 0 = 0, swap,
have h5' : f 0 * 2 = f 0 * m := by rw [mul_comm, h5, mul_comm],
have h7 := (domain.mul_right_inj h6).1 h5',
right,
use (f 0),
intro x,
convert h4 x,
rw h6 at h,
by_cases h7 : m = 0,
left,
intro x,
convert h4 x,
rw [h6, h7],
simp,
have h8 : 2 * m = m * m,
simpa using h 0 1,
have h8' : m * 2 = m * m,
rw [←h8, mul_comm],
replace h8 := (domain.mul_right_inj h7).1 h8',
right,
use (f 0),
intro x,
convert h4 x,
end
@lacker
Copy link

lacker commented Oct 6, 2020

similarly, also domain.mul_left_inj -> mul_left_inj'

Sign up for free to join this conversation on GitHub. Already have an account? Sign in to comment